On the Bachelor Program in Engineering Physics for underdeveloped and developing countries: vision for global competitiveness - Nugroho, Gunawan; Nasution, Aulia (Penerbit Universiti Kebangsaan Malaysia, 2019)
The importance of a Bachelor Program in Engineering Physics for underdeveloped and developing countries is discussed in this paper. Worldwide rapid developments need reliable engineering graduates with strong inter- and multidisciplinary academic qualifications. Anticipating this requirement, Bachelor degree program in engineering physics is regarded as the most suitable for preparing graduates in underdeveloped and developing countries with such qualification profile. Several studies showed that the need for such educational program is quite promising. The motivation to strive for higher qualifications is strong, and it is motivated by individual as well as the institutional consciousness, as also triggered by labor market requirements and government’s incentives. It is not surprising that the similar qualification profiles are already well designed in many industrial countries for Master up to PhD levels. Since the program requires a cross-discipline study among many fields, this paper also discusses the synergistic clustering strategy for facilitating the learning, research, and developmental activities. In this paper, seven clusters are proposed, namely generic knowledge, basic knowledge, instrumentation and control, energy and environmental engineering, materials, acoustics and vibration, and photonics. The cluster courses can be distributed in each semester depends on the department strategy of achieving the learning outcomes. Mandatory courses for such program are also being addressed as well.